Representaciones Sociales de tres Madres con Niños Diagnosticados con Trastorno de Déficit de Atención e Hiperactividad, en la ciudad de Bogotá. (2021)
The objective of the research was to identify the social representations in 3 mothers with children diagnosed with ADHD in the city of Bogota. It was based on Serge Moscovici's theories of social representations. Methodologically it was framed in the qualitative, phenomenological paradigm, as a technique and instrument for data collection was used the semi-structured interview, the population consisted of 3 mothers with children with ADHD.